Effects of Vocational Training on a Group of People with Intellectual Disabilities - Gomes-Machado, Maria Luiza; Santos, Flavia Heloisa [UNESP]; Schoen, Teresa; Chiari, Brasilia (Wiley-Blackwell, 2016)
Intellectual disability (ID) is the most restraining disability for professional inclusion, mainly due to the lack of adaptive skills focused on the work environment observed in people with ID. The aims of this study were (i) to describe and analyze the effects of a vocational training program on the adaptive behavior of people with ID and (ii) to evaluate the social impact of employability on the life of the employees with ID. Participants were 43 people with mild or moderate ID, age between 18 and 28 years. The Supports Intensity Scale was applied at two stages: T1-PRETRAINING and T2-POSTTRAINING, while the Social Impact Questionnaire was used at the third stage, after employment (T-3 POSTINCLUSION). The authors found that there were differences in total scores between stages T-1 and T-2 in relation to all the adaptive skills assessed, with a reduction of around 50% in the need for support. One year after inclusion in the labor market (T-3), participants were still employed, with significant improvements in such aspects as learning, autonomy, affective and social development, as well as in family and community relations. The vocational training contributed to the global development of persons, favoring their professional inclusion, and as a result, sustenance, autonomy, and a decrease in the need for assistance and support.
Keywords: intellectual disability; labor market; professionalization; vocational training